Prinsip Keadilan dalam Penetapan Wali Adhal: Analisis Yuridis Normatif Berdasarkan Hukum Islam dan Undang - Undang Perkawinan No.1 Tahun 1974 di Indonesia - Adila Putri Jasmin; Fachri Fachrudin; Muhammad Hidayat (AHKAM, 2026)
Refusal by a guardian in Islamic marriage (wali adhal) remains a persistent legal issue in Indonesia, particularly when the refusal is based on subjective considerations that are not rooted in sharia and when there is no explicit normative standard in the Kompilasi Hukum Islam (KHI) regarding “reasons justified by sharia.” This study aimed to analyze the juridical parameters for categorizing wali adhal and to evaluate the implementation of the principle of justice by judges of the Bogor Religious Court in deciding such cases in order to guarantee women’s right to marry. This study used a normative juridical approach through a combination of statutory, conceptual, and case analysis approaches. The results showed that Islamic law and Indonesian positive law share common ground in recognizing wali adhal when a guardian refuses a marriage without a valid syar‘i reason, but they differ in the degree of explicitness of their normative standards, thereby potentially causing inconsistency in judicial reasoning. Judges of the Bogor Religious Court showed a tendency toward substantive justice by prioritizing the principle of hifz al-nasl and the prevention of mudharat. This study concludes that wali adhal constitutes a deviation from the protective function of guardianship, so the principle of justice (‘adl) requires court decisions that provide substantive protection beyond the fulfillment of formal procedures. The contribution of this study lies in the formulation of three parameters of substantive justice in wali adhal cases, namely the factual foreseeability of the reasons for refusal, a recognized syar‘i basis, and active consideration of the prevention of harm.